2015
DOI: 10.1063/1.4934675
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the on-axis atom number density in the supersonic gas jet under high gas backing pressure by simulation

Abstract: The supersonic gas jets from conical nozzles are simulated using 2D model. The on-axis atom number density in gas jet is investigated in detail by comparing the simulated densities with the idealized densities of straight streamline model in scaling laws. It is found that the density is generally lower than the idealized one and the deviation between them is mainly dependent on the opening angle of conical nozzle, the nozzle length and the gas backing pressure. The density deviation is then used to discuss the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Thus it can be concluded that a conical nozzle with a long length and a big opening angle could be helpful to produce a supersonic gas jet with a radially uniform distribution of atom density, especially at a low height. These results can be understood as below: Because the lateral expansion becomes weak with the increase of the nozzle length and the opening angle, 21 it is reasonable that the l H become to be close to l, and the radial distribution tend to be uniform for a nozzle with a long length and a big opening angle at a given height. Meanwhile, as for the height dependence, because the increase of the height results in the TABLE III.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus it can be concluded that a conical nozzle with a long length and a big opening angle could be helpful to produce a supersonic gas jet with a radially uniform distribution of atom density, especially at a low height. These results can be understood as below: Because the lateral expansion becomes weak with the increase of the nozzle length and the opening angle, 21 it is reasonable that the l H become to be close to l, and the radial distribution tend to be uniform for a nozzle with a long length and a big opening angle at a given height. Meanwhile, as for the height dependence, because the increase of the height results in the TABLE III.…”
Section: Resultsmentioning
confidence: 99%
“…This results from the fact that the lateral expansion becomes strong as the gas expands from a conical nozzle under the high backing pressure. 21 This fact cannot be explained in the frames of the idealized straight streamline model, since this model provides a fixed structure of the jet for a given nozzle geometry (and a given gas species), which is independent of a gas backing pressure. It is noted that the relation between l T and l H can be obtained using η and η H .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations